2019
DOI: 10.1016/j.cmet.2018.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Imaging Reveals a Unique Preference of Symmetric Cell Division and Homing of Leukemia-Initiating Cells in an Endosteal Niche

Abstract: Graphical Abstract Highlights d SoNar serves as a unique tool for in vitro/in vivo studies of stem cell metabolisms d SoNar-high cells prefer glycolysis and are enriched for leukemia-initiating cells d Leukemia-initiating cells home to endosteal niches and prefer symmetric divisions d PDK2 sustains metabolic and leukemogenic activities of leukemia-initiating cells In Brief Hao et al. reveal that a genetically encoded metabolic sensor, SoNar, precisely monitors the metabolic status of leukemia-initiating cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Interestingly, most immunophenotypic Lin 2 Sca-1 1 c-Kit 1 CD150 1 CD48 2 adult HSCs were in the SoNar-mid cell population, as determined by flow cytometric analysis (supplemental Figure 5A-C). Because high SoNar ratios may represent greater glycolysis, as evidenced by a related biochemical analysis ( Figure 3) and our previous study, 41 these results indicate that adult HSCs may have a metabolic profile that differs from that of FL-HSCs. In addition, differentiated BM cells displayed a multilineage pattern that differed from that presented by the FL hematopoietic cells (supplemental Figure 5D).…”
Section: Fl-hscs and Adult Hscs Respond Differently To Nadh Shuttle Isupporting
confidence: 70%
“…Interestingly, most immunophenotypic Lin 2 Sca-1 1 c-Kit 1 CD150 1 CD48 2 adult HSCs were in the SoNar-mid cell population, as determined by flow cytometric analysis (supplemental Figure 5A-C). Because high SoNar ratios may represent greater glycolysis, as evidenced by a related biochemical analysis ( Figure 3) and our previous study, 41 these results indicate that adult HSCs may have a metabolic profile that differs from that of FL-HSCs. In addition, differentiated BM cells displayed a multilineage pattern that differed from that presented by the FL hematopoietic cells (supplemental Figure 5D).…”
Section: Fl-hscs and Adult Hscs Respond Differently To Nadh Shuttle Isupporting
confidence: 70%
“…Our knowledge of the leukemic bone marrow niche must greatly improve as many LSC vulnerabilities are, in part, niche-directed (reviewed elsewhere 215,216 ). Measuring metabolic alterations in the leukemic niche 77 , and using intravital microscopy 217 to visualise its three-dimensional cellular and histological sub-structures will be critical.…”
Section: [H1] Concluding Remarksmentioning
confidence: 99%
“…To further determine the changing metabolic preference during spermatogonial differentiation, we established a primary spermatogonial line containing a fluorescent cytosolic SoNar sensor, the intensity of which reflects the cytosolic NAD+ and NADH redox state 41 . In general, glycolysis produces NADH, which may be shuttled to mitochondria and oxidized to NAD+, or be recycled to NAD+ by lactate dehydrogenase (LDH) when generating lactate from pyruvate in the cytosol 42 . Therefore, the cytosolic NAD+/NADH ratio is determined by the net balance of these three pathways 42 .…”
Section: Metabolic Changes Upon Spermatogonial Differentiationmentioning
confidence: 99%
“…In general, glycolysis produces NADH, which may be shuttled to mitochondria and oxidized to NAD+, or be recycled to NAD+ by lactate dehydrogenase (LDH) when generating lactate from pyruvate in the cytosol 42 . Therefore, the cytosolic NAD+/NADH ratio is determined by the net balance of these three pathways 42 . We found that undifferentiated spermatogonia displayed a much higher NAD+/NADH ratio than that of differentiating spermatogonia induced by RA for 24 h (Fig.…”
Section: Metabolic Changes Upon Spermatogonial Differentiationmentioning
confidence: 99%